Synthesis of Elusive Chloropnictenium Ions. Issue 18 (17th March 2015) - Hering‐Junghans, Christian; Thomas, Max; Villinger, Alexander; Schulz, Axel
Abstract This work describes the synthesis and full characterization of elusive chloropnictenium ion salts of the type [RAr*N(SiMe)ECl][A] (RAr*=2, 6‐(CHPh2)‐4‐R‐C6H2, R=Me, tBu; E=Sb, Bi; A−=GaCl4, Al(OCH(CF3)2)4). In these species the cation is significantly stabilized by weak arene interactions to flanking phenyl groups of the RAr* moiety. In this context the bonding situation has been studied by computational means and the reactivity towards the Lewis base 4‐dimethylaminopyridine (dmap) was investigated.